Using Mobile Application as an Alternative to Pre-Writing Strategy - Noor Azilah Abdullah, Siti; Hashim, Harwati; Sofwan Mahmud, Muhammad (International Journal of Engineering and Technology, 2018)
Second language learners typically have problems in writing and producing a good writing product. This is strongly related to their inability of focusing on the most important stage of writing which is the pre-writing stage; the stage of producing ideas and key points. To overcome this issue, the use of mobile application named Pinterest as an alternative pre-writing strategy is definitely relevant in accordance to the 21st century teaching and learning. Therefore, this research aimed to identify the effectiveness of using Pinterest as an alternative pre-writing strategy and studentsâ€™ perception on the use of Pinterest in terms of advantages and disadvantages. A set of pre-test and post-test were given to 60 respondents followed by an online survey by 30 respondents at the end of the intervention. The findings revealed that the use of Pinterest as an alternative pre-writing strategy did actually help the respondents in writing. Based on the findings, it could be summarized that Pinterest as an alternative pre-writing strategy holds the opportunity of encouraging pre-writing and improving the writing process entirely. However, in order for students to fully benefit from the method, the challenges that deter the use of Pinterest need to be overcome. Â Â